RISK FACTORS OF DELAYS OF CHILD PHYSICAL DEVELOPMENT - T.I. Kaganova; O.V. Kuchumova ("Paediatrician" Publishers LLC, 2008)
Research targeted studying risk factors for delays physical development of children (n = 70) aged 7-11 years. Control group was comprised of 30 children of normal height of the same age. Physical development was evaluated by centile method using regional and international standards, studying data of life and disease anamnesis, family anamnesis, living conditions. Children had their thyroid glands studied ultrasonically. Blood levels of calcium, phosphor, magnesium, ferrum, zinc were identified by photometry method for some children in both groups. Correlation analysis makes it possible to state risk factors of children dwarfism: low educational status of parents, child height figures at the age of 1 and 3 years, calcium and phosphor blood levels, as well as thyroid hypo plasy.Key words: dwarfism, children, risk factors, calcium deficit.